(untitled) (International Journal of Engineering and Computer Science, 2016)
with continual advances in technology, coupled with increasing price/performance advantages, wireless accessibility is being deployed increasingly in office and public environments. This paper discusses the security threats and risks associated with wireless networks, and outline a number of best practices for deploying wireless networks in corporate and home environments. Finally, an Enhanced secure protocol for spontaneous wireless ad hoc networks which uses a hybrid symmetric/ asymmetric scheme and the trust between users in order to exchange the initial data and to exchange the secret keys that will be used to encrypt the data. Trust is based on the first visual contact between users. Proposed protocol is secure autonomous protocol and is not based on any infrastructure and external support in order to develop it over the devices with limited resources. Network creation, communication and management are the functionalities of the proposed system. A mechanism has been presented to allow the nodes to check the authenticity of their IP addresses while not generating any duplicated IP addresses. This mechanism helps nodes to authenticate by using their IP addresses. The proposed protocol has the following features Distributed security mechanism, Lightweight, Malicious user revocation capability.